The Relationship Between Case Manager Roles and Inpatient Operational Efficiency: A Cross-Sectional Study in Indonesian Referral Hospital. - Habibi, Zul; Saputra, Irwan; Martunis; Kamil, Hajjul; Usman, Said (International Journal of Nursing Education)
Background: Hospitals globally face increasing pressure to enhance operational efficiency without compromising care quality. In this context, the case manager role is pivotal, yet empirical evidence of its direct impact on quantitative efficiency metrics remains limited, particularly in developing countries. Objective: This study aimed to analyse the relationshipbetween case manager roles and the operational efficiency of inpatient wards at a public referral hospital in Indonesia. Material and Method: A cross-sectional design was employed, including all 39 head nurses selected through total sampling. Data were collected using a validated questionnaire assessing case manager roles, with high reliability (Cronbach's Alpha = 0.963). The Spearman Rho correlation test was used for analysis. Results: The results demonstratedthat the overall efficiency revealed that a significant majority of inpatient wards were classified as inefficient.Furthermore,a significant relationshipwas found between the overall role of case managers and operational efficiency (p = 0.036). Analysis of sub-variables also revealed significant relationships: coordination of health services (p=0.009), communication (p=0.048), care planning (p=0.024), prevention of intervention duplication (p=0.025), and supervision (p=0.046). Conclusion: The study concludes that despite a significant majority of inpatient wards (71.8%) being classified as inefficient, the case manager's role is significantly associated with key operational efficiency indicators. Therefore, optimizing this role through structured training, clear protocols, and enhanced interprofessional collaboration is recommended as a crucial strategy for hospital management to improve resource utilization and service quality.